Characteristics of Non-linguistic Cognitive Impairment in Post-stroke Aphasia Patients - Yao, Jingfan; Liu, Xinxin; Liu, Qi; Wang, Jinfang; Ye, Na; Lu, Xiao; Zhao, Yishuang; Chen, Hongyan; Han, Zaizhu; Yu, Miaoxin; Wang, Yu; Liu, Gaifen; et al. (Frontiers in Neurology, 2020)
Background: Non-linguistic cognitive training has been suggested to improve the communication skills of patients with post-stroke aphasia (PSA). However, the association between language and non-linguistic cognitive functions is not fully understood. In this study, we used the Loewenstein Occupational Therapy Cognitive Assessment (LOTCA) to evaluate the characteristics of non-linguistic cognitive impairments in Chinese PSA patients. Methods: A total of 86 stroke patients were recruited in this study. Language and non-linguistic cognitive impairments were evaluated by the Western aphasia battery (WAB) and LOTCA, respectively. The patients were divided into two groups (PSA and non-PSA), and the Chinese norm (the data came from 44 Chinese individuals without neurological disorders in a previous study) were used as the control group. The LOTCA scores were compared among the three groups. Patients in the PSA group were subdivided into the fluent aphasia group (FAG) and the non-FAG according to the Chinese aphasia fluency characteristic scale. The LOTCA scores were also compared between the PSA subdivisions. Potential confounders were adjusted in analysis of covariance. Partial correlation analysis between the sub-scores of WAB and LOTCA were also performed. Results: The total LOTCA scores in the PSA group (75.11±17.08) were significantly lower compared with scores in the non-PSA (96.80±7.75, P<0.001) and the control group (97.65±16.24, P<0.001). The PSA group also had lower orientation, visual perception (VP), spatial perception (SP), visuomotor organization (VMO), thinking operation (TO), and attention scores. The total LOTCA, orientation, VP, SP, and MP scores were lower in the non-FAG (69.24±18.06; 8.62±5.09; 12.76±2.47; 7.48±3.01; and 9.62±2.25, respectively) compared with the FAG (80.36±14.07; 12.14±3.99; 14.09±1.93; 9.68±3.01; 10.55±1.63, respectively, Ps<0.05). The aphasia quotient (AQ) was positively correlated with the total score of LOTCA and scores of orientation, VP, SP, and MP (r=0.710; r=0.744; r=0.565; r=0.597; r=0.616, P<0.001). Conclusion: Compared with stroke patients without aphasia, patients with PSA often have more extensive and serious non-linguistic cognitive impairments. Patients with non-fluent aphasia often present with serious cognitive impairments than those with fluent aphasia, especially the impairments of orientation and spatial perception. Non-linguistic cognitive impairments correlate with language impairments in aphasia.